Tổng hợp và đặc trưng của xúc tác SO42-/Al2O3-ZrO2 cấu trúc mao quản trung bình - Thuận và cộng sự, Ngô Thị (Vietnam Journal of Chemistry, 2014)
Two series of Al-promoted sulfated zirconia catalysts with 3% mol Al2O3 were prepared. In one case, Al-promoted mesostructured sulfated zirconia (Al-MSZ) catalysts have been synthesized from the template of the Pluronic P123 in queous solution. Zirconium and aluminum hydroxide has been prepared at 100oC under hydrothermal condition. In the other case, Al-promoted sulfated zirconia (Al-SZ) has been synthesized by the co-precipitation method. Al-SZ and Al-MSZ catalysts show high thermal stability. Al-MSZ catalysts show higher catalytic activity than Al-SZ.